Spatial analysis of nitrogen dioxide concentration in ambient air and its relationship to low birth weight incidence in Palembang City - Naqida, Naqida Rahma Fery; Dwi Septiawati; Elvi Sunarsih; Inoy Trisnaini; Laura Dwi Pratiwi (Science Midwifery, 2024)
One of the factors influencing the incidence of low birth weight (LBW) is exposure to air pollutants such as nitrogen dioxide (NO₂). Therefore, this study aims to analyze the relationship between NO₂ air pollution exposure and the incidence of LBW in Palembang City. This research uses an ecological study design with secondary data obtained from the Palembang City Health Office, the Palembang City Environmental Office, and the Regional Development Planning and Research Agency (Bappeda Litbang) of Palembang. Data analysis was conducted using Geographic Information Systems (GIS). The study focused on seven subdistricts as sampling locations based on air monitoring points established by the Environmental Office. The results of the study show that the highest number of LBW cases was found in Ilir Timur I Subdistrict, with 58 cases in 2022. Meanwhile, the highest NO₂ concentration was recorded in Plaju Subdistrict, reaching 266 µ/NM³/hour in 2020. Overlay analysis indicated no significant relationship between NO₂ concentration and LBW incidence in most areas, except in Plaju Subdistrict during 2020-2021, where both NO₂ concentrations and the number of LBW cases were relatively higher compared to other subdistricts.